2012
DOI: 10.1071/ahv36n3_re
|View full text |Cite
|
Sign up to set email alerts
|

The future of community-centred health services in Australia: 'When too many beds are not enough'

Abstract: The authors welcome a constructive debate on the future of community-centred health services. Therefore, we have written this piece in response to an article published by Cunningham in the previous edition of the Australian Health Review (Cunningham, Australian Health Review 2012; 36: 121-124), which was a very limited analysis and misleading critique of our previous contribution to this journal (Rosen et al. Australian Health Review 2010; 34: 106-115). The focus here is necessarily brief and does not stand in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5][6] We have had more than 20 years of warnings that the mental health system is built on a hospital-based and fragmented model, which promotes neither recovery nor inclusion. 1,7,8 Despite the evidence reiterated in recent reports, [1][2][3][4][5] there are few signs of change.…”
Section: Introductionmentioning
confidence: 61%
“…[1][2][3][4][5][6] We have had more than 20 years of warnings that the mental health system is built on a hospital-based and fragmented model, which promotes neither recovery nor inclusion. 1,7,8 Despite the evidence reiterated in recent reports, [1][2][3][4][5] there are few signs of change.…”
Section: Introductionmentioning
confidence: 61%
“…Although one could argue that ‘too many beds’ is not the solution, it is important to recognize the high acuity of adolescents admitted to inpatient care (Rosen et al . ). One Canadian study sample found that 87% of admitted adolescents had thoughts of injuring themselves prior to admission, 77% did engage in nonsuicidal self‐injury (NSSI), and 67% had made an attempt to end their life prior to admission (Preyde et al .…”
Section: Introductionmentioning
confidence: 97%
“…In terms of access to care, many countries continue to struggle with the limited number of adolescent inpatient beds to meet the demand (Buchanan 2014;Geller & Biebel 2006;Kadvany 2015;Mackee 2018;Merrillees 2014). Although one could argue that 'too many beds' is not the solution, it is important to recognize the high acuity of adolescents admitted to inpatient care (Rosen et al 2012). One Canadian study sample found that 87% of admitted adolescents had thoughts of injuring themselves prior to admission, 77% did engage in nonsuicidal self-injury (NSSI), and 67% had made an attempt to end their life prior to admission (Preyde et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, shortcomings in the process of deinstitutionalisation, largely political and economic, mean the development of community mental health services has been inadequate and is being eroded. [5][6][7][8][9] Although approximately 70 jurisdictions worldwide have schemes enabling involuntary community treatment orders (CTOs), 10 they remain extremely controversial. There is much debate arising from what is a heterogeneous evidence base for their effectiveness, as well as a range of ethical, legal and political dilemmas raised by their use, including issues surrounding the use of coercion and the accountability of health practitioners and policy makers to provide adequate mental health and other social services.…”
Section: Introductionmentioning
confidence: 99%